Musculoskeletal pain in Europe: its impact and a comparison of population and medical perceptions of treatment in eight European countries. Issue 4 (12th March 2004) - Woolf, A D; Zeidler, H; Haglund, U; Carr, A J; Chaussade, S; Cucinotta, D; Veale, D J; Martin-Mola, E
Abstract : Objectives: To describe the impact of musculoskeletal pain (MP); to compare management of MP by the population and by primary care physicians; and to identify misconceptions about treatment. Methods: 5803 people with MP and 1483 primary care physicians, randomly selected, in eight European countries were interviewed by telephone. A structured questionnaire was used to ask about usual management of MP and perceived benefits and risks of treatment. Current health status (SF-12) was also assessed. Results: From primary care physicians' perceptions, MP appears to be well managed. All presenting patients are offered some form of treatment, 90% or more doctors are trying to improve patients' quality of life, and most are aware and concerned about the risks of treatment with NSAIDs. From a population perspective, up to 27% of people with pain do not seek medical help and of those who do, several wait months/years before seeing a doctor. 55% or fewer patients who have seen a doctor are currently receiving prescription treatment for their pain. Communication between doctors and patients is poor; few patients are given information about their condition; and many have misconceptions about treatment. Conclusions: Management of MP is similar across eight European countries, but there is discordance between physician and patient perspectives of care. Some people with pain have never sought medical help despite being in constant/daily pain. Those who do seek help receive little written information or explanation and many have misperceptions about the benefits and risks of treatment that limit their ability to actively participate in decisions about their care.